Methods for concentration of urinary immunoreactive insulin. - Du, B. H. (Korean Academy of Medical Sciences, 1986)
Insulin is readily concentrated from 10 to 50 ml of urine with better than 75% recovery using octadecylsilyl (ODS) silica columns (C18Sep-Pak cartridge) and can then be measured by radioimmunoassay. Fractionation on Sephadex G50 gel filtration reveals that the apparent immunoreactivity corresponds for the most part to 6000 dalton insulin. Renal clearance of insulin in 5 normal subjects does not appear to differ in the fasted or fed state and ranged from 0.34 to 0.58 ml/min with an average of 0.44 +/- 0.10 (S.D.) ml/min. Increased urinary insulin output was observed following feeding and fell during prolonged fasting. Insulin output in urine from 7 non-diabetic subjects ranged from 11 to 39 mU/24 hr, averaging 25 +/- 10 mU/24 hr. In normal subjects without renal disease a single determination of renal insulin clearance and a timed urinary insulin output appear to be sufficient for determination of mean plasma insulin during that time period. Concentration of urine using this methodology could provide the material for HPLC screening for abnormal insulins and for their subsequent purification to determine the site of change in amino acid sequence.